I am too old for this! barriers contributing to the non-adoption of mobile payment - Cham, Tat Huei; Cheah, Jun Hwa; Cheng, Boon Liat; Lim, Xin Jean (Emerald Publishing, 2022)
Purpose: Since its inception, mobile payment is rapidly gaining popularity over the years, and starting to replace traditional modes of payment. The usage of mobile payments has further escalated following various precautionary measures (i.e. social distancing) in curbing the transmission of the COVID-19 outbreak. However, most of the elderlies are still sceptical about the usage of mobile payment services. The current study was set to investigate the impact of functional, psychological and risk barriers that resulted in elderlies' resistance towards using such services. The impact of stickiness to cash was also examined as a moderator on the investigated relationships. Design/methodology/approach: Online survey questionnaires were used to collect the responses from 400 elderly consumers at the age of 60 and above. Data analysis was then performed using the SPSS and AMOS statistical software packages. Findings: Findings obtained acknowledged the significance of functional (i.e. perceived complexity, perceived incompatibility and perceived cost), psychological (i.e. lack of trust, inertia, and technological anxiety) and risk (i.e. privacy risk, security risk, financial risk and operational risk) barriers in influencing resistance towards mobile payment services among the elderlies. Consequently, resistance would influence their attitude and non-adoption intention; with attitude as the mediator between resistance and non-adoption intention. Finally, moderation analysis also confirmed the moderating effect of stickiness to cash towards elevating the correlation between resistance and non-adoption intention. Originality/value: This study is one of the very few studies that explored the minimally investigated territory on the consequential importance of mobile payment usage among the elderlies, specifically, through extending the literature on the impact of functional, psychological and risk barriers towards the individuals' resistance. Besides, this study also successfully contributed to existing body of knowledge by highlighting the mediating role of attitude and moderating role of stickiness to cash in the interrelationships between resistance, attitude and non-adoption intention.